2014
DOI: 10.1093/neuonc/nou047
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic index, microvascular proliferation, and necrosis define 3 groups of 1p/19q codeleted anaplastic oligodendrogliomas associated with different genomic alterations

Abstract: The present study shows that oligodendrogliomas with classic histological features remain a molecularly heterogeneous entity and should be stratified according to 1p/19q status because of its major prognostic relevance. Moreover, 1p/19q codeleted AOs are also heterogeneous. Interestingly, mitotic index, MVP, and necrosis help to classify them into 3 groups associated with distinct genomic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
7
40
0
2
Order By: Relevance
“…Mitotic index and Mib1 proliferative index were higher, as expected, in high grade OG and AS compared to their lower grade counterparts [23,24] but did not otherwise affect OS. Intratumoral calcifications were observed in both OG and AS as well-described in the literature [10,23] and correlated with a better OS in univariate and multivariate analysis. Very few studies report the link between calcification and a better prognosis in gliomas [26,27] and it has been suggested that calcification might be a consequence of the slow growth and indolent course of a less-aggressive tumor [28].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Mitotic index and Mib1 proliferative index were higher, as expected, in high grade OG and AS compared to their lower grade counterparts [23,24] but did not otherwise affect OS. Intratumoral calcifications were observed in both OG and AS as well-described in the literature [10,23] and correlated with a better OS in univariate and multivariate analysis. Very few studies report the link between calcification and a better prognosis in gliomas [26,27] and it has been suggested that calcification might be a consequence of the slow growth and indolent course of a less-aggressive tumor [28].…”
Section: Discussionsupporting
confidence: 56%
“…The presence of MVP in OGs was not correlated to OS, unlike that reported by some authors [10,24,25]. In ASs the presence of MVP was sufficient for a diagnosis of GBM [23] thus a correlation with poor prognosis was not surprising.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Most importantly, they lack IDH1 R132H expression, which is common in most 1p19q codeleted oligodendrogliomas. 14 Moreover, in contrast to 1p19q codeleted oligodendrogliomas, which show strong and intense Olig2 expression, Olig2 expression in clear cell ependymomas remains rare and never exceeds 20% of nuclei when recorded.…”
Section: Discussionmentioning
confidence: 99%
“…De plus, l'analyse molé culaire montre clairement une hé té rogé né ité molé culaire au sein des oligodendrogliomes anaplasiques purs (aussi appelé s CFO pour classic form of oligodendroglioma) puisque même si 80 % d'entre eux pré -sentent la codé lé tion 1p19q, les 20 % restant ont un profil molé culaire qui s'apparente aux glioblastomes. Ainsi, il devient indispensable de distinguer le sous-groupe des oligodendrogliomes anaplasiques codé lé té s du fait de leur pronostic nettement meilleur et peut-ê tre, à terme, de ré server la dé nomination d'oligodendrogliome à ce seul sous-groupe [11]. L'é tude molé culaire de la sé rie POLA ré vè le par ailleurs que la mutation IDH isolé e est l'apanage des gliomes mixtes anaplasiques et que les glioblastomes à composante oligodendrogliale (grade IV dans la classification de l'OMS 2007) forment un groupe histo-molé culaire et pronostic hé té rogè ne, posant la question du maintien de cette entité dans la future classification de l'OMS (Figarella-Branger et al, soumis pour publication).…”
unclassified